2019
DOI: 10.3390/ijms20133124
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide Association Study of Karnal Bunt Resistance in a Wheat Germplasm Collection from Afghanistan

Abstract: Karnal bunt disease of wheat, caused by the fungus Neovossia indica, is one of the most important challenges to the grain industry as it affects the grain quality and also restricts the international movement of infected grain. It is a seed-, soil- and airborne disease with limited effect of chemical control. Currently, this disease is contained through the deployment of host resistance but further improvement is limited as only a few genotypes have been found to carry partial resistance. To identify genomic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 37 publications
(53 reference statements)
1
15
0
Order By: Relevance
“…Previous studies reported the presence of KB resistance loci scattered on many chromosomes in all three genomes of wheat 15,16 . Hence, cultivar pyramiding/stacking of favourable alleles from multiple loci is a prerequisite to develop KB resistance 22 .…”
Section: Linkage Disequilibrium Analysis and Genome-wide Association mentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies reported the presence of KB resistance loci scattered on many chromosomes in all three genomes of wheat 15,16 . Hence, cultivar pyramiding/stacking of favourable alleles from multiple loci is a prerequisite to develop KB resistance 22 .…”
Section: Linkage Disequilibrium Analysis and Genome-wide Association mentioning
confidence: 95%
“…Therefore, KB resistance is controlled by minor additive and epistatic loci. Previous studies using bi-parental populations and a GWAS panel have reported additive QTLs for KB resistance 2,15,16 , but information on epistatic QTL is lacking. This report is the first to identify additive and epistatic QTL for KB resistance in a GWAS panel.…”
Section: Linkage Disequilibrium Analysis and Genome-wide Association mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 11 articles in the Special Issue on plant genes conferring resistance to biotic stresses [3,[25][26][27][28][29][30][31][32][33][34], seven articles reported results from single resistant genes (or QTL) for crops and plant species, including soybean, rice, wheat, Dasypyrum villosum, Aegilops searsii, Capsicum annuum, and Vitis quinquangularis. The other four articles [27,29,30,32] analyzed multiple QTLs or genomic regions for one or more diseases.…”
Section: Chromosomal Distribution Patterns Of Genes For Abiotic-stresmentioning
confidence: 99%
“…In the Special Issue, "Mapping Abiotic Stress-Tolerance Genes in Plants" of International Journal of Molecular Sciences, 21 papers, including two reviews and 19 research articles, were published . Eleven research articles [3,[25][26][27][28][29][30][31][32][33][34] were published in the Special Issue "Mapping Plant Genes that Confer Resistance to Biotic Stress. "…”
Section: Introductionmentioning
confidence: 99%